Very early feeding in stable small for gestational age preterm infants: a randomized clinical trial - Shmuel Arnon; Daniella Sulam; Fred Konikoff; Rivka H. Regev; Ita Litmanovitz; Timna Naftali (Brazilian Society of Pediatrics, 2013)
Objective: To examine the effect of initiating very early feeding on time-to-reach full feeding in stable, small for gestational age (SGA) preterm infants. Method: Preterm infants with gestational age below 37 weeks and birth weight below the 10th percentile were randomly allocated to a very early (within 24 hours of birth) feeding regimen or delayed (after 24 hours of birth) feeding. All infants had in utero evidence of absent or reverse diastolic flow. Infants unable to start early feeding were excluded. Time-to-reach full feeding, feeding progression, and related morbidity were compared. Electrogastrography (EGG) was used to measure pre- and postprandial gastric motility on the second and seventh day after feeding initiation. Results: Sixty infants were included in the study, 30 in each group. Infants included in the very early feeding regimen achieved full enteral feeding sooner than controls (98±80-157 vs. 172±123-261 hours of age, respectively; p = 0.004) and were discharged home earlier (p = 0.04). No necrotizing enterocolitis (NEC) was documented in both study groups. Gastric motility was improved at day seven after feeding initiation in both study groups, with no difference between groups. Conclusions: Stable SGA preterm infants on a very early feeding regimen achieved full enteral feeding and were discharged home significantly earlier than those on a delayed regimen, with no excess morbidity.